Religion and Discrimination: A Review Essay of Persecution and Toleration: The Long Road to Religious Freedom - Iyer, Sriya (Journal of Economic Literature, 2022)
Noel D. Johnson and Mark Koyama’s book, Persecution and Toleration: The Long Road to Religious Freedom, examines the links between religion, state action, and the development of liberalism in medieval Europe. It discusses a model of “conditional toleration”; how the interaction between religion and state influences persecution and discrimination against minorities; and how religious freedom eventually paved the way for scientific advances, liberalism, and economic growth. It tackles issues such as fiscal capacity, anti-Semitism in Europe, plagues including the Black Death, heresy in the Spanish Inquisition, witchcraft trials, the Holocaust, climate shocks, and the growth of cities with emergent religious minorities. It discusses these issues for a range of countries in medieval Europe, providing rich historical detail and interpretive depth for its main argument. This is a deeply evocative book that makes an important contribution to the new economics of religion. Carefully researched and thoughtfully crafted, the themes it discusses and the ideas it raises have relevance not only for medieval European societies, with which it is principally concerned, but also for contemporary economies everywhere. (JEL D72, N13, N33, N43, Z12)